Classification of English and Russian Concepts on Construction Industry - YAHIN, MARAT AJDAROVICH; SAKAEVA, LILIYA RADIKOVNA; BAZAROVA, LILIYA VYAZIROVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research reveals specific details in classifying and systematizing english and russian construction industry terms in a comparative aspect which help to identify aspects of this thesaurus: physical characteristics, style, materials, elements, equipment, and activities. The given classifications of construction industry can’t be made without its careful analysis. The sublanguage of modern construction industry has universal properties characteristic of a common language and differential properties that are not found in that type of language. Classes of terms unify the largest groups of terms in hierarchical relationships in construction terminology and reflect the conceptual categories of independent sections of the industry. RESUMEN Esta investigación revela detalles específicos en la clasificación y sistematización de los términos de la industria de la construcción en inglés y ruso en un aspecto comparativo, que ayuda a identificar aspectos de este tesauro: características físicas, estilo, materiales, elementos, equipos, y actividades. Las clasificaciones dadas de la industria de la construcción no se pueden hacer sin un análisis cuidadoso. El sublenguaje de la industria de la construcción moderna tiene propiedades universales características de un lenguaje común y propiedades diferenciales que no se encuentran en ese tipo de lenguaje. Las clases de términos unen las agrupaciones de otros términos mayores en relaciones jerárquicas en la terminología de la construcción y reflejan las categorías conceptuales de secciones independientes de la industria.